PENGARUH STRATEGI CUSTOMER RELATIONSHIP MANAGEMENT DAN TEKNOLOGI INFORMASI TERHADAP PERILAKU WORD OF MOUTH (Studi Pada Klaster Batik Tulis Lasem di Rembang) - Syaiko Rosyidi (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2015)
The purpose of this study was to examine the role of Customer Relationship Management (CRM) and Information Technology (IT) on the behavior of Word of Mouth (WOM) consumers Batik Tulis Lasem in Rembang Regency. The phenomenon of collaborative CRM strategy with the use of IT has become the trend of an increasingly competitive strategy and economical. The research location is on a cluster Batik Tulis Lasem which includes the District of Lasem and the District Pancur using survey method, the type of the data subject and the data source is primary with a questionnaire instrument by using purposive sampling of 140 respondents and involve 52 businesses Batik Tulis Lasem. Research data will be analyzed using multiple linear regression analysis.The results showed that both independent variables CRM (X1) and TI (X2) has positive and significant effect on the behavior of WOM (Y) consumers Batik Tulis Lasem.Keywords: Customer Relationship Management, Information Technology, and Word of Mouth.